Pengaruh Literasi Keuangan dan Sikap Keuangan Pribadi Terhadap Perilaku Keuangan Mahasiswa - Yasmin Aisy Salwa, Arizah; Abdillah, Nashiruddin; Matus Sa’diyah, Anik; Ayu Setiawati, Riska (Teewan Journal Solutions, 2025)
This research seeks to examine the impact of financial literacy and personal financial attitudes on the financial behavior of Management students at Sunan Ampel State Islamic University in Surabaya. The study employs a quantitative methodology, gathering data through online questionnaires. Data analysis was conducted using SmartPLS version 3.2.9. The findings reveal that financial literacy does not significantly influence students' financial behavior, whereas personal financial attitudes have a notable positive effect. These results imply that the enhancement of financial education programs should prioritize the cultivation of positive financial attitudes to foster improved financial behavior. It is anticipated that these insights will serve as a foundation for universities in developing pertinent curricula aimed at strengthening students' managerial competencies in addressing future financial challenges.